P95 Developing a public benchmarking table aligned with national audit quality improvement priorities in pulmonary rehabilitation. (December 2018) - Mortier, K; Steiner, M; McMillan, V; Holzhauer-Barrie, J; Lowe, D; Roberts, CM
Abstract : Introduction: The National COPD Audit Programme conducted an audit aiming to capture all patients enrolled on to a pulmonary rehabilitation (PR) course between 3 January and 31 March 2017 in England and Wales. Alongside this an audit of the resources and organisation of PR services was conducted in England and Wales between 3 January and 28 April 2017. Public benchmarking was developed in order to summarise each service's performance against its peers, in order to identify areas of focus for quality improvement activities. Methods: In order to create a meaningful benchmarking table six key indicators were identified and categorised into process and outcome performance indicators. These indicators were selected as they were objective and easily recordable, mapped to accepted quality standards and discriminatory in the audit cycle. Results: 7476 patients (79% of those eligible) were included in the clinical audit submitted from 184 services. 187 (96%) services participated in the organisational audit. Services results for the six key indicators were split according to the national median. An additional column was added referring to case ascertainment for PR services derived from the total number of cases submitted by services to the clinical audit divided by the number of eligible patients reported by services in the organisational audit. Each of the quartiles both above and below the median were colour coded to assist in identifying their performance nationally compared to their peers. This enabled services at a glance to identify areas of focus that required improvement. Conclusion: The benchmarking of results is a clear and efficient way to show both variations and similarities across services. Using the three main colours services are able to quickly identify both best performance and gaps in processes. Benchmarking can help to set performance expectations enable a culture of continuous improvement.